Profile of selected cardiovascular disease risk factors among HIV patients on anti-retroviral therapy in Bushbuckridge Sub-District, Mpumalanga Province - Mathebula, Rudy Londile (My University, 2019)
The purpose of this study was to profile selected cardiovascular disease risk factors among HIV patients on ART in Bushbuckridge sub-district. Quantitative, crosssectional research was conducted to describe cardiovascular disease risk factors among HIV patients on ART in Bushbuckridge Sub-district. Data collection was done using researcher-administered questionnaires. Adult HIV patient on ART participated in the study (n=328). The study has highlighted cardiovascular disease risk factors and prevalence of cardiovascular disease risk factors among HIV patients on ART. The findings revealed the prevalence of hypertension is 34.6% among HIV patients on ART and men had a higher prevalence compared to women. There is an increase in body mass index and it is seen mostly among women. Alcohol consumption is highest in the young adults (18 to 24 years) both men and women. Health promotion and policymaking interventions need to improve strategies on management and prevention of cardiovascular disease risk factors. Key concepts HIV, ART, cardiovascular disease risk factors, prevalence, body mass index, Bushbuckridge
Thesis (MPH.) -- University of Limpopo, 2019
Keywords: HIV/AIDS; ART; Cardiovascular disease risk factors; Prevalence; Body mass index; Bushbuckridge; HIV-positive persons; Body mass index; Human body -- Composition